Bounty Hunter - Tennant, Andy, 1955-; Aniston, Jennifer; Butler, Gerard, 1969-; Baranski, Christine (Culver City, Calif. : Sony Pictures Home Entertainment, 2010)
"Milo Boyd (Gerard Butler 300, The Ugly Truth), a down-on-his-luck bounty hunter, gets his dream job when he is assigned to track down his bail-jumping ex-wife, reporter Nicole Hurly (Jennifer Aniston, TV's 'Friends'). He thinks all that's ahead is an easy payday, but when Nicole gives him the slip so she can chase a lead on a murder cover-up, Milo realizes that nothing ever goes simply with him and Nicole. The exes continually one-up each other - until they find themselves on the run for their lives."--Container.
DVD release of the 2010 motion picture.
Special features: Join Jennifer Aniston and Gerard Butler on the set in making The bounty hunter and on location with stops along the road to learn more about shooting this hilarious comedy. Also includes the rules for outwitting a bounty hunter!
2.35:1 anamorphic widescreen.
Bilingual packaging (English/French).
"Keep your enemies close. Keep your ex closer."--Container.
Columbia Pictures presents in association with Relativity Media ; an Original Film production ; an Andy Tennant film ; produced by Neal H. Moritz ; written by Sarah Thorp ; directed by Andy Tennant.
Keywords: Bounty hunters -- Drama; Fugitives from justice -- Drama; Romantic comdey films; DVD-Video discs; Action; Action and adventure films; Drama; Feature films